Case report: Biliobronchial fistula after biliary tract stenosis - Batalin Júnior, Luís Maurício [UNESP]; Zandoná, Mariana Conceição e Silva Seleme [UNESP]; Vargas, Thomaz Almeida [UNESP]; Oliveira, Julio Cesar de [UNESP]; Chiappetto, Juliana Rocha Souza [UNESP]; Oliveira, Cassio Vieira [UNESP]; Romeiro, Fernando Gomes [UNESP]; Tanni, Suzana Erico [UNESP] (Frontiers, 2022)
Biliobronchial fistula (BBF) is a rare abnormality resulting from congenital or acquired communication between the bile ducts and the bronchial tree. Patients often suffer from chronic cough, dyspnea, and bilioptysis, a pathognomonic symptom of this condition. Conservative methods such as less-invasive procedures are gradually consolidating. Nonetheless, surgery remains the primary treatment, especially in more complex cases. We present the case of a 44-year-old woman with a chronic cough, no verified periods of fever, cyclic jaundice, and episodes of yellowish sputum. She had undergone cholecystectomy in 2018 and had been hospitalized several times since for pneumonia treatment. All consequent investigations for mycobacteriosis were negative. When referred to our hospital, she had cyclic jaundice and parenchymal consolidation in the right lower lobe. Suspected bilioptysis motivated the search for a biliobronchial fistula. Magnetic resonance cholangiography (MRC) confirmed stenosis of the biliary tract and fistulous path, and sputum analysis indicated high bilirubin levels. External biliary bypass was performed as an initial conservative and definitive therapy due to the presence of liver cirrhosis. Although BBF is a rare condition when bilioptysis is suspected, a diagnostic investigation should be initiated. Our case study proposes two criteria for diagnosis: an imaging exam demonstrating the fistulous path and confirmation of bilirubin in the sputum or bronchoalveolar lavage (BAL). When diagnosed, surgical correction should be performed.
Keywords: biliary tract stenosis; biliobronchial fistula; bilioptysis; cyclic jaundice; pneumonia